2014
DOI: 10.1007/s00421-014-2923-9
|View full text |Cite
|
Sign up to set email alerts
|

Circadian rhythm of peripheral perfusion during 10-day hypoxic confinement and bed rest

Abstract: Daytime vasoconstriction induced by hypoxia and/or bed rest is abolished at night, lending further support to the theory that changes in peripheral skin temperature may be functionally linked to sleep onset.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 32 publications
1
18
0
Order By: Relevance
“…observed a progressive decrease in subjects' skin temperature during 35 days of horizontal bedrest, with changes particularly obvious in distal body regions, and with the most pronounced temperature decrements observed at the tips of the toes, suggesting that cutaneous vasomotor tone increased gradually during the course of the bedrest. During sustained hypoxic exposure, cutaneous vasoconstriction was shown to increase from day 1 to day 10, especially in lower extremities (McDonnell et al, 2014). Yogev et al (2010), on the other hand, observed no significant difference in ΔT forearm-fingertip and ΔT calf-toe between days 1 and 22 of bedrest, a finding which is in agreement with the observations in the present study when comparing days 10 and 20 with baseline values within all three experimental conditions.…”
Section: Body Temperature and Proximal-to-distal Skin Temperature Grasupporting
confidence: 94%
See 2 more Smart Citations
“…observed a progressive decrease in subjects' skin temperature during 35 days of horizontal bedrest, with changes particularly obvious in distal body regions, and with the most pronounced temperature decrements observed at the tips of the toes, suggesting that cutaneous vasomotor tone increased gradually during the course of the bedrest. During sustained hypoxic exposure, cutaneous vasoconstriction was shown to increase from day 1 to day 10, especially in lower extremities (McDonnell et al, 2014). Yogev et al (2010), on the other hand, observed no significant difference in ΔT forearm-fingertip and ΔT calf-toe between days 1 and 22 of bedrest, a finding which is in agreement with the observations in the present study when comparing days 10 and 20 with baseline values within all three experimental conditions.…”
Section: Body Temperature and Proximal-to-distal Skin Temperature Grasupporting
confidence: 94%
“…The subjects in our study did not wear socks during the experiment, and could hence have been experiencing regional discomfort by feeling cold during the course of the one-hour trial, especially due to exaggerated cutaneous vasoconstriction, induced by prolonged hypoxia and/or bedrest McDonnell et al, 2014). It is therefore conceivable that, in all three conditions, they could have regulated T wps at a higher level than in a normoxic ambulatory condition to outbalance the discomfort associated with cold feet.…”
Section: Thermal Comfort Ratingmentioning
confidence: 83%
See 1 more Smart Citation
“…The study was part of the 'LunHab: Lunar Habitat Simulation' project investigating the effects of a 10 day hypoxic bedrest on several functions of cardiorespiratory and musculoskeletal systems (see Debevec et al 2014;McDonnell et al 2014;Salvadego et al 2016). The study was part of the 'LunHab: Lunar Habitat Simulation' project investigating the effects of a 10 day hypoxic bedrest on several functions of cardiorespiratory and musculoskeletal systems (see Debevec et al 2014;McDonnell et al 2014;Salvadego et al 2016).…”
Section: Ethical Approvalmentioning
confidence: 99%
“…McDonnell et al . ; Keramidas et al . ), it is an area that is worthy of more attention, as is the associated field of ‘cross‐adaptation’.…”
Section: Introductionmentioning
confidence: 99%